Effect of colletotrichum dematium var. Truncata and phomopsis sojae in sanitary and physiological quality of soybean seeds. - Galli, Juliana Altafin [UNESP]; Panizzi, Rita de Cássia [UNESP]; Vieira, Roberval Daiton [UNESP] (My University, 2007)
Several pathogens can affect the quality of soybean seeds. With the objective of evaluating the transport of fungi through seeds from soybean plants artificially inoculated in field conditions, with two isolates of C. dematium var. truncata and one isolate of P. sojae and their effects on the sanitary and physiologic quality of seeds, four soybean varieties (BRS 133, MSoy 6101, Conquista and Liderança) were sowed in field. Each block was inoculated with C. dematium var. truncata isolate 1 and isolate 2, P. sojae, and a block without inoculation (control). The seeds were manually harvested and were submitted to the Blotter test, initial water content, 100 seeds weight, germination in roll paper and emergence in sand. The seeds presented a high infection for Fusarium spp.. Phomopsis sojae was found in all the treatments, and its incidence was related with the incidence of Fusarium sp. in seeds. There were differences in pathogenicity among isolates of C. dema-tium var. truncata, being the isolate 1 the most pathogenic one, specially for the variety Liderança (25% of infection for C. dema-tium var. truncata). Fusarium sp. influenced negatively the germination of variety MSoy 6101, independently of treatment, and C. dema-tium var. truncata affected negatively the germination of varieties Conquista and Liderança. The values of germination in sand were significantly higher than germination in paper, for the varieties MSoy 6101, Conquista and Liderança.
Efeito de colletotrichum dematium var. Truncata e phomopsis sojae na qualidade sanitária e fisiológica de sementes de soja
Keywords: Anthracnose; Germination; Glycine max; Stem blight